Face mask fit modifications that improve source control performance - Blachere, Francoise M.; Lemons, Angela R.; Coyle, Jayme P.; Derk, Raymond C.; Lindsley, William G.; Beezhold, Donald H.; Woodfork, Karen; Duling, Matthew G.; Boutin, Brenda; Boots, Theresa; Harris, James R.; Nurkiewicz, Tim; et al. (American journal of infection control, 2022)
•Face masks reduce the expulsion of respiratory aerosols (called source control).•Poorly fitted masks allow respiratory aerosols to escape through face seal leaks.•Fit modifications improve the performance of face masks as source control devices.•Unmodified medical masks blocked ≥56% of cough aerosols and ≥42% of exhaled aerosols.•An elastic brace over a mask blocked ≥95% of cough and ≥99% of exhaled aerosols. During the COVID-19 pandemic, face masks are used as source control devices to reduce the expulsion of respiratory aerosols from infected people. Modifications such as mask braces, earloop straps, knotting and tucking, and double masking have been proposed to improve mask fit however the data on source control are limited. The effectiveness of mask fit modifications was determined by conducting fit tests on human subjects and simulator manikins and by performing simulated coughs and exhalations using a source control measurement system. Medical masks without modification blocked ≥56% of cough aerosols and ≥42% of exhaled aerosols. Modifying fit by crossing the earloops or placing a bracket under the mask did not increase performance, while using earloop toggles, an earloop strap, and knotting and tucking the mask increased performance. The most effective modifications for improving source control performance were double masking and using a mask brace. Placing a cloth mask over a medical mask blocked ≥85% of cough aerosols and ≥91% of exhaled aerosols. Placing a brace over a medical mask blocked ≥95% of cough aerosols and ≥99% of exhaled aerosols. Fit modifications can greatly improve the performance of face masks as source control devices for respiratory aerosols.